Examination of the sickness experience for the year 1935 of persons insured under the National Health Insurance Acts - O Brolchain, R. (Statistical and Social Inquiry Society of Ireland, 1939)
There are approximately 500,000 persons in the State engaged in gainful occupation either as manual workers or as clerical workers with a rate of remuneration not exceeding #250 per annum. This bulk may be taken as a representative group and is the only particularised group in the nation in which it is possible to measure from existing data the incidence of sickness and disease in the working population. This is the first time that any figures of the incidence of sickness of those insured under the National Health Insurance Acts have been made available. It would probably be advisable at the outset to explain the source of the information, the type of member dealt with and other similar details. Who are these 500,000 and whence comes this particular information?
Read on Friday, 21th January, 1939
Keywords: National health insurance; Cause of death; 314.15